A Simple Approach to Biological Single‐Cell Lasers Via Intracellular Dyes. Issue 9 (21st May 2015) - Nizamoglu, Sedat; Lee, Kyung‐Bok; Gather, Malte C.; Kim, Ki Su; Jeon, Mijeong; Kim, Seonghoon; Humar, Matjaž; Yun, Seok‐Hyun
<x xml:space="preserve">Abstract</x> Biological cell lasers based on biocompatible fluorescent molecular probes are demonstrated. Instead of time‐consuming genetically encoded gain, the new approach yields a fast and simple method to obtain lasing from single cells. This method also facilitates lasing of adherent mammalian cells.